Information Structure and Reference Tracking in Complex Sentences. - Gijn, Rik van (Typological studies in language ;, 2014)
This paper discusses argument marking and reference tracking in Mekens complex clauses and their correlation to information structure. The distribution of pronominal arguments in Mekens simple clauses follows an absolutive pattern with main verbs. Complex clauses maintain the morphological absolutive argument marking, but show a nominative pattern with respect to argument reference tracking, since transitive and intransitive subjects function as syntactic pivots. The language extends the use of argument-marking verb morphology to control the reference of discourse participants across clauses.